2017
DOI: 10.1073/pnas.1715053114
|View full text |Cite
|
Sign up to set email alerts
|

Mapping allele with resolved carrier status of Robertsonian and reciprocal translocation in human preimplantation embryos

Abstract: Reciprocal translocations (RecT) and Robertsonian translocations (RobT) are among the most common chromosomal abnormalities that cause infertility and birth defects. Preimplantation genetic testing for aneuploidy using comprehensive chromosome screening for in vitro fertilization enables embryo selection with balanced chromosomal ploidy; however, it is normally unable to determine whether an embryo is a translocation carrier. Here we report a method named "Mapping Allele with Resolved Carrier Status" (MaReCs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 39 publications
0
35
0
1
Order By: Relevance
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…All but four studies reported a statistically significant reduction in the percentage of embryos suitable for transfer before and after PGT‐A. The remaining four studies most likely failed to reach statistically significant differences due to the small sample size . As a direct consequence of this, opting for PGT‐A will most likely increase the risk of experiencing a cycle with no transferable embryos and patients should therefore be informed about this risk during counseling on when to opt for PGT‐A or not, as well as about the ongoing discussion of a clinical effect.…”
Section: Discussionmentioning
confidence: 99%
“…MaReCs could improve the accuracy of breakpoint determination to approximately 200 kbp, reducing the current range limitation of informative SNPs to approximately 1 Mbp flanking the breakpoint. Therefore, this improvement reduces risk of misdiagnosis caused by recombination of the analyzed embryo . However, this method also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of misdiagnosis will increase if the proband embryos only have trisomic translocated chromosomes. In this instance, it may be necessary to analyze a second polar body or sperm cell in female or male carriers, respectively, to establish the haplotype phase …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation